How teacher questioning can reduce the cognitive demand of mathematical tasks - Åsmund Gjære; Reidar Mosvold (LUMAT)
This study investigates the impact of teacher questioning on the cognitive demand of mathematical tasks within the context of the Developmental Education in Mathematics (DEM) reform initiative in Norway. Using a case study design, researchers’ video-recorded and analyzed twelve lessons by four primary teachers. The analysis focused on the function of teacher questions within classroom dialogues around challenging tasks. Findings reveal that while DEM emphasizes challenging tasks and conceptual understanding, teacher questioning often inadvertently simplifies problems, limiting students’ opportunities for learning and development. This tendency is exacerbated by DEM’s focus on rapid progression, which can conflict with the need for students to dwell on tasks that are challenging for them. The study underscores the need for teacher training to navigate the complexities of balancing rapid progression with student-led exploration and conceptual understanding.